We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
32
1
avatar+134 

What is the simplest form of the radical expression?

 3^3√2a − 6^3√2a

 Apr 30, 2019
 #1
avatar+5097 
+1

\(3^3\sqrt{2a}-6^3\sqrt{2a}=\\ \sqrt{2a}\left(3^3-(3\cdot 2)^3\right)=\\ \sqrt{2a}3^3(1-2^3) = \\ 27\sqrt{2a}(-7) = \\ -189\sqrt{2a}\)

.
 May 2, 2019

9 Online Users